The Attributed Work To Sibawayh Outside His Book: Analytical Examples - Al-Marshudi, Abdulwahid Bin Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Sibawayh is the pioneer in grammar and morphology, and his book forms the basis for many subsequent Arabic books. Incorrect attributions could transfer to later grammatical works, leading to erroneous judgments and attributions of opinions. He understands Sibawayh's opinion through his book and observes his statements, evidence, and explanations. The aim is to pave the way for authenticating the views of prominent scholars who influenced the development, foundation, and refinement of Arabic, especially in books composed after the 5th century Hijri. The researcher endeavored to collect examples from some leading figures in Arabic studies who encountered such discrepancies. The results: most of the opinions that should have been attributed to Sibawayh resulted from scholars needing to understand Sibawayh's phrases and intentions, issuing judgments based on the apparent understanding rather than the actual context. Some opinions attributed to Sibawayh outside his book pertain to lost books like 'Al-Wadih' and 'Al-Basit.' This indicates missing links in specific passages of the book, prompting scholars of Sibawayh's heritage to examine and attempt to fill these gaps, which undoubtedly will contribute novelty to the book and its texts.